Unveiling Sentiment and Financial Risks: OJK’s 10% Co-Payment in Health Insurance - Kesuma, Muhammad Ramadhani; Irianto, Ellen D. Oktanti; Henrika, Margareth; Ariswati, Lusiana Desy; Aini, Rohana Nur; Widaryo, Chandika Mahendra (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This qualitative study explores public sentiment and thematic discourse surrounding the Otoritas Jasa Keuangan (OJK) regulation mandating a 10% co-payment for health insurance claims, effective January 1, 2026, as outlined in SEOJK No. 7/SEOJK.05/2025. Data were collected from X posts and associated replies between May 20 and June 12, 2025, a period justified by its alignment with the regulation’s announcement and initial public reaction phases. Employing thematic coding inspired by NVivo 12 methodologies, five key nodes emerged: Regulation Announcement, Cost Concerns, Consumer Criticism, Industry Perspective, and Policy Clarification. Analysis reveals a predominant neutral sentiment in initial media-driven posts, contrasted by a strong negative sentiment in public replies, reflecting financial burdens and trust erosion. The study leverages a word cloud to highlight recurring terms like “co-payment,” “cost,” and “OJK,” reinforcing public focus on financial implications. Findings indicate a reputational risk for insurers and OJK, necessitating enhanced consumer engagement and policy communication. This research contributes a novel perspective on real-time social media sentiment analysis in regulatory contexts, addressing a gap in understanding public response to health insurance reforms in Indonesia. Implications suggest targeted educational campaigns and stakeholder consultations to mitigate adverse perceptions.